EVALUATION OF THE STATUS OF PRENATAL SCREENING AND DIAGNOSIS OF DOWN SYNDROME AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Evaluation of the status of prenatal screening and diagnosis of Down syndromeSubjects and methods: Retrospective, cross-sectional descriptive study on 33 fetuses and 73children diagnosed with Down syndrome at Center for prenatal and neonatal diagnostic andscreening – Nghe An Obstetrics and Pediatrics Hospital from 7/2020 to 7/2022Results: Fetal ultrasound is a common prenatal screening method, providing the indication forprenatal diagnosis (amniocentesis). There were 2/33 (6%) fetus of Down syndrome with normalfetal ultrasound but positive Trisomy 21 NIPT. Amniocentesis implemented after 20 weeks had6/33 (18,2%) cases. In 73 Down syndrome children: 15/73 (29.5%) cases with abnormalities onfetal ultrasound were recorded when information was collected from the family; screening bymaternal blood (Double test/Triple test/NIPT) was performed in 11/73 cases, accounting for15.1%.Conclusion: Combining maternal serum screening/NIPT with periodic ultrasound (under theguidance of the Ministry of Health) would help early prenatal diagnosis of DS. Raising awarenessabout prenatal screening and diagnosis for families in Nghe An and surrounding areas is anextremely vital issue.
Keywords: Down syndrome, prenatal screening, prenatal diagnosis.